1975
DOI: 10.1002/pol.1975.180131112
|View full text |Cite
|
Sign up to set email alerts
|

Random‐coil dimensions of poly(methylphenylsiloxane) and their dependence on stereochemical structure

Abstract: Rotational isomeric state theory was used to study the unperturbed dimensions 〈r2〉0 of poly(methylphenylsiloxane) (PMPS) chains [Si(CH3)(C6H5)O]x as a function of their stereochemical structure. The required conformational energies were obtained from semi‐empirical, interatomic potential energy functions and from known results on poly(dimethylsiloxane). PMPS chains were found to differ from monosubstituted and disubstituted vinyl chains primarily in the larger distance of separation between groups in conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…One may then conclude that the excellent agreement found between experiment and the RIS calculations indicates that intermolecular interactions do not significantly influence the PMPS mean-squared dipole moment; the temperature dependence of 〈μ 2 〉 must have an intramolecular origin. An important intramolecular interaction was elucidated by Mark et al . They applied the RIS model, calculated 〈 r 0 2 〉/ nl 2 for PMPS chains, and found an attractive interaction between phenyl rings on adjacent skeletal silicon atoms.…”
Section: Resultsmentioning
confidence: 99%
“…One may then conclude that the excellent agreement found between experiment and the RIS calculations indicates that intermolecular interactions do not significantly influence the PMPS mean-squared dipole moment; the temperature dependence of 〈μ 2 〉 must have an intramolecular origin. An important intramolecular interaction was elucidated by Mark et al . They applied the RIS model, calculated 〈 r 0 2 〉/ nl 2 for PMPS chains, and found an attractive interaction between phenyl rings on adjacent skeletal silicon atoms.…”
Section: Resultsmentioning
confidence: 99%
“…6 Theoretical calculations of these properties have been performed by matrix multiplication methods and by Monte Carlo techniques. [20][21][22][23][24][25][26][27][28] In all cases, a fixed geometry for the molecule was used: fixed bond lengths and bond angles, plus rotational isomers also at fixed positions, either as discrete states 20,23,24,27 or allowing a small oscillation around these states. 21,22,25,26,28 However, recent calculations by Mattice et al on PDMS 29,30 and other poly(dialkylsiloxanes) 31,32 have shown the need for a more realistic description of siloxane chains.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that PMPS has a dipole moment ratio similar to that of PDMS and PDES. Therefore, the substitution in a siloxane chain of an alkyl side group for a phenyl group yields very similar values of (µ 2 )/nm 2 , though the intramolecular interactions change significantly (as a consequence of a particularly strong energy preference for C 6 H 5 • · · C6H 5 interactions 31 ). In all the cases the difference between them is less than 20%.…”
Section: Discussionmentioning
confidence: 62%